KOMUNITAS LAMUN DI PERAIRAN PESISIR PULAU YAMDENA, KABUPATEN MALUKU TENGGARA BARAT - Keppel, Rene Ch; Baulu, Sandra (Sam Ratulangi University, 2011)
This study was aimed at identifying the seagrass, and knowing the seagrass community structure in the coastal waters of Yamdena Island, West Southeast Maluku. This study was carried out from July to September 2007. The highest density was shown by C. rotundata in Olilit, T. hemprichii in Lauran and Kabiarat, and E. acoroides in Kabiarat and Watmasa. Furthermore, the highest abundance of seagrass occurred by C. rotundata in Olilit, H. pinifolia in Lauran, T. hemprichii in Kabiarat, and E. acoroides in Watsama. The highest occurrence was shown by C. rotundata in Olilit, E. acoroides in Lauran, T. hemprichii in Kabiarat and Lauran, and H. pinifolia dan H. ovalis in Watmasa.Keywords: Seagrass, community, Yamdena Island, West Southeast Maluku